Dearomatization Reactions of Indoles to Access 3D Indoline Structures - Abou-Hamdan, Hussein; Kouklovsky, Cyrille; Vincent, Guillaume (Synlett, 2020)
This Account summarizes our involvement in the development of dearomatization reactions of indoles that has for origin a total synthesis problematic. We present the effort from our group to obtain 3D-indolines scaffold from the umpolung of N-acyl indoles via activation with FeCl3 to the oxidative spirocyclizations of N-EWG indoles and via the use of electrochemistry.1 Introduction2 Activation of N-Acyl Indoles with FeCl32.1 Hydroarylation of N-Acyl Indoles2.2 Difunctionalization of N-Acyl Indoles3 Radical-Mediated Dearomatization of Indoles for the Synthesis of Spirocyclic Indolines4 Electrochemical Dearomatization of Indoles4.1 Direct Electrochemical Oxidation of Indoles4.2 Indirect Electrochemical Oxidation of Indoles5 Conclusion
Keywords: indole; dearomatization; indolines; FeCl3; radical chemistry; electrochemistry